Values that influence employment acceptance among physical therapists practicing in primary care shortage and non-urban designation areas - Patti Berg-Poppe; Joy Karges-Brown; Adam Ladwig; Patrick Cross (James Cook University, 2021)
Introduction: Physical therapists (PTs) in all United States, DC, and the US Virgin Islands have first-contact direct access privileges to examine and treat patients. Evidence supports the value of PT services in reducing annual healthcare costs, decreasing the need for prescription pain medication, and decreasing the need for outpatient physician care. PTs can play an essential role in managing patient health needs in primary care health professional shortage areas (pcHPSAs), especially in rural areas, which are disproportionately affected by shortage-related health disparities. The current study examined values that differentiated PTs who accept and maintain employment in pcHPSAs and non-urban areas, as a means of advising health agencies within these designation areas. Methods: A survey invitation was emailed to PTs in six states. The Determinants of Employment Acceptance Survey was used to survey the importance of six factors (attachment to place, community assets, practice environment, professional advancement, relationships, and remuneration) when considering employment. Results: Respondents included 373 PTs (36% pcHPSA; 33% non-urban). Professional advancement was significantly more important to PTs intending to continue their employment in a pcHPSA. Community assets were more important to PTs in non-urban areas who planned to leave their employment within 5 years. The most valued factors for PTs, regardless of practice location, were practice environment and attachment to place. Conclusion: Employers in rural areas or pcHPSAs who are interested in recruiting and retaining PTs should consider the importance of professional advancement, practice environment, and workplace relationships, and should use strategic measures to fortify these assets within the workplace.